NGOs AND THE INSTITUTIONAL DEVELOPMENT OF MEMBERSHIP ORGANISATIONS THE CASE OF THE QUILON FISHERMEN WELFARE SOCIETY - Mick Howes and Suresh Balakrishnan (IDS Discussion Paper 371, 1999)
Recent shifts in NGO and donor priorities make it important to understand how NGOs promote membership organisations. As a means of exploring this issue, this paper uses the example of the largely successful NGO attempts to help South Indian fishermen organise in response to technical change. Key factors are found to have contributed to the process of institutional development that has taken place. A strong indigenous NGO presence has provided continuity, enabling international NGOs to confine themselves to the financial and technical functions that they are best able to discharge. A clear core of mutually supporting activities has been identified around which people have been able to organise. At the same time, institutional development is revealed to be a long-term undertaking, which depends at least partly on chance, and in which difficult trade-offs may have to be made between equity and sustainability.